Mepolizumab in the management of severe eosinophilic asthma in adults: current evidence and practical experience. (January 2017) - Varricchi, Gilda; Bagnasco, Diego; Ferrando, Matteo; Puggioni, Francesca; Passalacqua, Giovanni; Canonica, Giorgio W.
Eosinophils represent approximately 1% of peripheral blood leukocytes in normal donors and their maturation and differentiation in the bone marrow are mainly regulated by interleukin (IL)-5 [Broughton et al. 2015]. IL-5, a cytokine that belongs to the β common-chain family, together with IL-3 and granulocyte-macrophage colony-stimulating factor (GM-CSF), stimulates also the activation and survival of eosinophils and, to some extent, of basophils. IL-5 binds to a heterodimer receptor composed of the specific subunit IL-5Rα and a common subunit βc shared with IL-3 and GM-CSF. Human eosinophils express approximately a three-fold higher level of IL-5Rα compared with basophils. Major sources of IL-5 are T-helper 2 (Th2) cells, mast cells, CD34+ progenitor cells, invariant natural killer (NK) T-cells, group 2 innate lymphoid cells (ILC2s), and eosinophils themselves. ILC2s control not only eosinophil number but also their circadian cycling through the production of IL-5.